A native predator utilising the invasive brown marmorated stink bug, Halyomorpha halys (Hemiptera: Pentatomidae) as a food source. Issue 7 (3rd July 2017) - Biddinger, David J.; Surcică, Alex; Joshi, Neelendra K.
ABSTRACT: The nest provisions of a native predator species Bicyrtes quadrifasciata (Say) (Hymenoptera: Crabronidae) were surveyed and examined for the presence of nymphs of Halyomorpha halys, which is an invasive pest of many economically important agricultural crops in the U.S.A. We found 96% of the nest provisions of B. quadrifasciata were H. halys indicating the potential of B. quadrifasciata in biocontrol of this pest. Potential of B. quadrifasciata in regulating population dynamics of H. halys is discussed.